Search for resonant production of tt̄ pairs in 4.8fb-1 of integrated luminosity of pp̄ collisions at √s=1.96TeV - Aaltonen, T; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2011)
We search for resonant production of tt̄ pairs in 4.8fb-1 integrated luminosity of pp̄ collision data at √s=1.96TeV in the lepton+jets decay channel, where one top quark decays leptonically and the other hadronically. A matrix-element reconstruction technique is used; for each event a probability density function of the tt̄ candidate invariant mass is sampled. These probability density functions are used to construct a likelihood function, whereby the cross section for resonant tt̄ production is estimated, given a hypothetical resonance mass and width. The data indicate no evidence of resonant production of tt̄ pairs. A benchmark model of leptophobic Z′→tt̄ is excluded with m Z′<900GeV/c2 at 95% confidence level. © 2011 American Physical Society.